Competition in the workplace: An experimental investigation - Volker Benndorf; Holger A. Rau (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2012)
We analyze competition between workers in a gift-exchange experiment where two workers are hired by the same employer. In the competition treatment the two employees simultaneously choose their effort whereas in the baseline treatment competition cannot occur since there is only one employee per employer. We find that in the competition treatment employers implicitly set tournament incentives by rewarding employees who choose higher effort levels than their co-workers. Here, employees' effort levels increase significantly faster, which can be explained by imitation learning. Furthermore we find that employers decrease their wage payments per unit of effort exerted over time when employing two workers.
Keywords: C91; J41; L22; M52; 330; Gift Exchange; Competition; Internal Organization; Multiple Employees